2013
DOI: 10.1007/s12471-013-0485-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-aortic balloon counterpulsation in acute myocardial infarction: old and emerging indications

Abstract: BackgroundRecent evidence questions the role of intra-aortic balloon counterpulsation (IABP) in the treatment of acute myocardial infarction (AMI) complicated by cardiogenic shock (CS). An area of increasing interest is the use of IABP for persistent ischaemia (PI). We analysed the use of IABP in patients with AMI complicated by CS or PI.MethodsFrom 2008 to 2010, a total of 4076 patients were admitted to our hospital for primary percutaneous coronary intervention (PCI) for AMI. Out of those, 239 patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…From a pathophysiological point of view, the main feature of death in AMI-cardiogenic shock is unstable hemodynamics with reduced systolic and mean arterial pressures that lead to reduced oxygen supply to vital organs [ 9 ], while the IABP can give hemodynamic support to these hemodynamically unstable patients by increasing blood flow to the heart and decreasing the cardiac workload [ 2 ]. However, the reason why the mortality of AMI-cardiogenic shock patients was not sufficiently reduced may be because the effects on cardiac output are modest [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a pathophysiological point of view, the main feature of death in AMI-cardiogenic shock is unstable hemodynamics with reduced systolic and mean arterial pressures that lead to reduced oxygen supply to vital organs [ 9 ], while the IABP can give hemodynamic support to these hemodynamically unstable patients by increasing blood flow to the heart and decreasing the cardiac workload [ 2 ]. However, the reason why the mortality of AMI-cardiogenic shock patients was not sufficiently reduced may be because the effects on cardiac output are modest [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis of Van Nunen et al. showed that the outcome in these patients is favorable and mandates further prospective studies. Another clinical scenario resembling these conditions exists inside the patient after coronary bypass surgery with good bypasses but transient myocardial stunning due to prolonged extracorporeal circulation .…”
Section: Discussionmentioning
confidence: 99%
“…IABP use should therefore be considered where effective revascularisation cannot immediately be delivered or where the device's effects may ameliorate severe or prolonged peri-procedural ischaemia. The SEMPER FI trial, currently in recruitment and due to complete in December 2018, will address this hypothesis 31). Common such situations include patients awaiting primary revascularisation with CABG or with acute mitral regurgitation or ventricular septal defects.…”
Section: Evidence For Use In Cardiogenic Shockmentioning
confidence: 99%